Perlindungan Hukum bagi Pembeli atas Hak Milik Tanah dalam Menikmati Fungsi dan Manfaat Tanah sebagai Pemegang Hak Milik - Bayu Sagita Damopolii; Imam Koeswahyono; Moh. Fadli (Perspektif Hukum, 2017)
In the process of buying and selling land as the basis for the transition of land rights from the seller to buyers in the area of Bolaang Mongondow, especially in Lolak Village District Lolak is done in two ways, namely the process of buying and selling as in general the sale and purchase of land ownership is a unity of land and buildings and plants above it and the process of buying and selling of land is not a unity between the land and buildings and plants above it or the sale and purchase by using the principle of separation horizontal is separate sale and purchase. However, in the development of the practice of the process of buying and selling land that is considered as part of the process of buying and selling property rights on customary land or customary law, it raises legal problems, the process of buying and selling property rights on land that can not provide legal protection of the status of property in full for the buyer in the land and enjoy the benefits and functions of the land itself.